Large‐Area Multicolor Emissive Patterns of Quantum Dot–Polymer Films via Targeted Recovery of Emission Signature. Issue 4 (11th January 2016) - Malak, Sidney T.; Jung, Jaehan; Yoon, Young Jun; Smith, Marcus J.; Lin, Chun Hao; Lin, Zhiqun; Tsukruk, Vladimir V.
Abstract : A facile one‐step fabrication of large‐area multicolored emissive photopatterns in mixed quantum dot‐polymer films is demonstrated. This is in sharp contrast to the current photopatterning approaches that utilize only a single quantum dot (QD) component for single‐color patterns. Strategies are presented that allow for either selective or collective modification of specific predetermined photoluminescent peaks of green and red QDs during photopattern development. These strategies yield novel patterns and allow for unprecedented control over how the color contrast of the photopattern evolves with continuous light illumination. These results clearly show that the evolution of the emission spectra of a multicolor mixed QD‐polymer film can be readily tailored during pattern development, either by careful selection of the excitation wavelength or through combinations of controllably unstable and stable QDs with different recovery rates. Notably, these strategies are simple, fast, and robust, yielding high‐resolution microscopic patterns over large areas (up to fractions of a cm 2 ). Furthermore, the flexibility and capabilities of these strategies greatly expand the potential applications of multicolor emissive photopatterns, particularly in the areas of sensing, imaging, and lasing systems where it is important to exert delicate control over the intensity of selected colors within specific spatial regions. Abstract : Large‐area multicolor patterning of quantum dot‐polymer films is achieved via targeted recovery of the emission signature.